THE EFFECTIVENESS OF HEURISTIK VEE LEARNING MODEL ASSISTED WITH PERDU/EDUCATIVE GAMES (EG) WORKSHEET TOWARDS THE STUDENTS’ LEARNING RESULT ON PLANT MOVEMENT MATERIAL - Rohmawati, Mei Dewi; Setiati, Ning; Susilowati, Sri Mulyani Endang (Unnes Science Education Journal, 2017)
Abstract ___________________________________________________________________ This study aims to determine student learning outcomes in learning to use the Heuristic Vee-assisted learning model with LKS PERDU. Material of Motion on Plants in MTs Muhammadiyah 3 Masaran Sragen was employed for the study. This study uses a quasi-experimental design. The sample used is a class VIII A (experimental group) and VIII C (control group). Sampling technique was the purposive sampling. The results showed> 75% of student learning outcomes exceed the minimum completeness criteria (KKM) is 75. Cognitively, the average grade student mastery learning experiment was 90% while the control group 77%. In psychomotor aspect in the experimental class 79.2% of students qualify as very good, and the rest on both criteria. On the affective aspects in the experimental class 75% of students qualify as very good, and the rest on both criteria. In general, teachers and students also respond very well to be applied learning. Conclusions from this research is learning by learning model Heuristic Vee student learning outcomes, student psychomotor, and affective student in plant material Motion class VIII MTs Muhammadiyah 3 Masaran Sragen.